2005
DOI: 10.3758/bf03192733
|View full text |Cite
|
Sign up to set email alerts
|

Normative data for semantically associated Spanish word lists that create false memories

Abstract: The present study provides norms for Spanish word lists that have been used to create false memories in native speakers of Spanish. The word lists reported are based on the Roediger and McDermott (1995) lists that have been used extensively to examine illusory memories. We employed Roediger and McDermott's critical lures, translated them into Spanish, and created semantically associated Spanish word lists by testing native Spanish speakers. The resulting lists were then normed with additional native Spanish sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 16 publications
3
16
1
2
Order By: Relevance
“…The level of recall in the present study differed somewhat from those reported by Stadler et al (1999) and Anastasi, De Leon, and Rhodes (2005), but the patterns were similar. For example, Stadler et al found that a greater proportion of list items (.60) were recalled than critical lures (.40).…”
Section: Recall Datacontrasting
confidence: 57%
See 4 more Smart Citations
“…The level of recall in the present study differed somewhat from those reported by Stadler et al (1999) and Anastasi, De Leon, and Rhodes (2005), but the patterns were similar. For example, Stadler et al found that a greater proportion of list items (.60) were recalled than critical lures (.40).…”
Section: Recall Datacontrasting
confidence: 57%
“…This table also provides the proportions of list items and critical lures recalled in the English and Spanish lists normed in previous studies (Anastasi, De Leon, & Rhodes, 2005;Roediger & McDermott, 1995;Stadler et al, 1999). The data from the Italian lists showed great variability in the probabilities that the different lists would produce illusory memories.…”
Section: Recall Datamentioning
confidence: 99%
See 3 more Smart Citations